Evaluation of Rice (Oryza sativa L.) Genotypes at Germination and Early Seedling Stage for Their Tolerance to Salinity - Islam, MM; Karim, MA (The Agriculturists, 2011)
An experiment was conducted at the Laboratory of Agronomy Department, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur from July-June, 2009-2010 to evaluate the rice (Oryza sativa L.) genotypes for their tolerance to salinity. One hundred rice genotypes and two check cultivars (Pokkali as tolerant and IR29 as susceptible) were exposed to solution of Electrical Conductivity (EC) of 10, 15, and 20 dSm-1 (5:1 molar concentration of NaCl and CaCl2 solution) at germination and early seedling stage. Based on visual salt injury symptoms at 15 dSm-1, 13 genotypes were found fairly tolerant to salinity. However, among the 13 genotypes, only Patnai23 showed higher germination index and seedling relative dry weight than the check salt tolerant Pokkali at 15 dSm-1. Beside these, performance of Awned-1, Nonasail and Soloi was also well at this level. The genotypes Patnai23, Awned-1, Nonasail and Soloi showed the best performance under saline condition. Keywords: Rice genotypes; germination; salinity; tolerance DOI: 10.3329/agric.v8i2.7578 The Agriculturists 8(2): 57-65 (2010)